Outcomes of fracture-related infections – do organism, depth of involvement, and temporality count? - Janus S H Wong; Alfred L H Lee; Christian Fang; Henry C H Leung; Alicia H Y Liu; Ryan C K So; Colin S Y Yung; Tak-Man Wong; Frankie Leung (Journal of Orthopaedic Surgery, 2022)
Purpose: To determine mortality and outcomes of patients diagnosed with fracture-related infections (FRIs). Methods: FRI patients treated at a trauma centre between 2001 and 2020 were analysed. The primary outcome was 1-year mortality; mortality associations with FRI organism, depth of involvement, and temporality were investigated with multivariable survival analysis. Healthcare-associated and serological outcomes were reported as secondary outcomes. Results: 311 FRIs with mean age of 67.0 and median Charlson comorbidity index of 0 were analysed. Methicillin-sensitive Staphylococcus aureus (MSSA) (29.9%) was the most frequently implicated organism. The majority of FRIs were deep infections (62.7%). FRIs were diagnosed at a median of 40 (IQR 15–200) days post index surgery. The mean follow-up was 5.9 years. One-year mortality amounted to 17.7%. MSSA FRIs were associated with better survival (adj HR 0.34, 95%CI 0.15–0.76, p = 0.008). There was no difference in survivorship between deep or superficial FRI (adj HR 0.86, 95%CI 0.62–1.19, p = 0.353) or in relation to onset time (adj HR 1.0, 95%CI 0.99–1.00, p = 0.943). Implant removal or debridement alone was performed in 61.7% and 17% respectively. Antibiotics was prescribed for 53 (IQR 23–110) days, and patients were hospitalised for 39 (IQR 19–78) days. CRP and ESR normalised in 70.3% (median 46 days) and 53.8% (median 86 days) patients respectively. Conclusion: Fracture-related infections are associated with significant mortality and morbidity regardless of depth and temporality. Non-MSSA FRIs are associated with inferior survival.